Cerebral Venous Sinus Thrombosis following Ventriculoperitoneal Shunting for Idiopathic Intracranial Hypertension. (4th March 2022) - Luckett, John P.; Sotoudeh, Houman; Tabibian, Borna E.; Markert, James M.; Kline, Lanning B.
ABSTRACT: A 30-year-old woman with idiopathic intracranial hypertension experienced worsening headaches and decreasing vision in her left eye. She underwent an uncomplicated ventriculoperitoneal shunt procedure but the following day was found to have cerebral venous sinus thrombosis. Treatment included venous sinus thrombectomy and anticoagulation. She had a favourable clinical outcome. Extensive evaluation including testing for thrombophilia was unremarkable. Potential causes for this rare association are discussed.